Handbook for assessing and managing care in the community - Philip Seed; Gillian Kaye (London ; J. Kingsley, 1994)
This practical book covers the complex issues involved in assessment procedures and care management and is addressed care to managers and to social care providers at all levels. Including sample forms and using many examples, it explains in clear terms the implications of various approaches. The reader is shown not only how best to carry out assessments, but also the broader meaning and context of specific assessment tasks.
The book is informed by recent research, including major research funded by the Scottish Office which focused on adults with learning difficulties. Implications are also drawn from the author's broader experiences of working with other client group.
Keywords: Disability Peoples; Social Services; Social Sciences